Mobilizing FDI for sustainable infrastructure investment - Munir Akram (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
Private investments in infrastructure projects for developing countries are critical to achieving the Sustainable Development Goals and net-zero carbon emissions. Due to structural limitations, however, their contribution remains limited. This Perspective suggests that the United Nations can help to overcome those limitations, creating a global model for sustainable infrastructure investment.
Keywords: 330